Pautas espaciales en la evolución de la estructura agraria del Prepirineo oscense (1962-1999) - Heredia Laclaustra, A.; Frutos Mejías, L. M. (Geographicalia, 2016)
The spatial organisation of mediterranean mountain is highly affected by the evolution of the agricultural activities and structure. Demographic and socioeconomic changes during the last fifty years have led these areas to be disregarded; the abandonment of the traditional activities, which have modelled its landscapes, is one of the most outstanding effects. The study area: Prepirineo oscense, is used as an example of this situation. The recent evolution analysis of the agrarian structure, and its relationships with demographic transforrnations, will allow us to assess the intensity of the happened changes and its spatial behaviour.